2022
DOI: 10.3390/jcm12010186
|View full text |Cite
|
Sign up to set email alerts
|

Mid- and Long-Term Atrio-Ventricular Functional Changes in Children after Recovery from COVID-19

Abstract: Background: Although most children may experience mild to moderate symptoms and do not require hospitalization, there are little data on cardiac involvement in COVID-19. However, cardiac involvement is accurately demonstrated in children with MISC. The objective of this study was to evaluate cardiac mechanics in previously healthy children who recovered from severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection in a long-term follow-up by means of two-dimensional speckle-tracking echocardiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…On the other hand, the results regarding the impairment of myocardial longitudinal strain after SARS-CoV2 infection were in line with previously published data [ 19 , 21 , 38 ] on both children and adult patients with an asymptomatic or mildly symptomatic COVID-19 course, demonstrating a slight but significant reduction in cardiac longitudinal deformation in children with a previous SARS-CoV-2 infection compared to those who were only vaccinated.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…On the other hand, the results regarding the impairment of myocardial longitudinal strain after SARS-CoV2 infection were in line with previously published data [ 19 , 21 , 38 ] on both children and adult patients with an asymptomatic or mildly symptomatic COVID-19 course, demonstrating a slight but significant reduction in cardiac longitudinal deformation in children with a previous SARS-CoV-2 infection compared to those who were only vaccinated.…”
Section: Discussionsupporting
confidence: 91%
“…The methodology for STE analysis was previously described [ 19 , 21 ]; it was performed by two experienced echocardiographers blind to the clinical data and COVID-19 vaccination status.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the long-term clinical impact of infection due to different variants was not assessed. In the same pediatric cohort, we have previously observed that 157 children and adolescents who experienced an asymptomatic or mild COVID-19 during the Parental and Delta waves showed a significant increase in left ventricular myocardial deformation abnormalities compared to 107 age and body surface area-comparable healthy controls −20.5% ± 2.9% vs. −21.8% ± 1.7%; p < 0.001) ( 30 , 31 ). Moreover, we observed that the incidence of left ventricular myocardial deformation abnormalities persisted higher in COVID-19 cases compared to healthy controls up to 148 days after infection ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 80%
“…However, in adult studies, sequelae such as myocarditis, chronic heart failure and postural orthostatic tachycardia syndrome have been reported among patients who had recovered from acute infection ( 45 , 46 ), which also suggest the necessity of operating non-invasive examinations in children. In research assessing ventricular function, it was found that children may develop chronic left ventricular deformation and dysfunction, which may be related to chronic inflammation of myocardium ( 47 ). Another study speculated that the changes might be related to the destruction of the myocardial mitochondria ( 48 ).…”
Section: Clinical Manifestation Of Long Covid In Different Systemmentioning
confidence: 99%